Digestible threonine-to-lysine ideal ratio for laying hens fed with low-protein diets from 24 to 40 weeks of age - Pastore,Silvana Marques (2016)
ABSTRACT: This trial was performed to determine the dietary digestible threonine-to-lysine (dig. Thr-to-Lys) ideal ratio for laying hens fed with low-protein diets from 24 to 40 weeks of age. At 24 weeks of age, two hundred forty Hy Line W-36 laying hens were randomly assigned to five treatments, represented by five dig Thr-to-Lys ratios (60; 67; 74; 81 and 88%), with eight replicates each one with six hens per experimental unit. Digestible Thr-to-Lys did not affect laying hen performance and egg quality, except for digestible Threonine intake, which showed linear increase as dig. Thr-to-Lys ratios increased. Linear broken-line model was chosen to analyze data according to lack of fit. According to linear broken-linen estimates, digestible Threonine ideal levels for optimum egg production, egg mass, feed efficiency of lysine utilization for egg mass, feed conversion per egg mass and dozens of eggs and nitrogen balance were 0.610; 0.580; 0.614; 0.599; 0.599 and 0.643%, which correspond respectively to dig Thr-to-Lys ratios of 80; 75; 80; 78; 78 and 83%. The digestible threonine-to-lysine ideal ratio for laying hens from 24 to 40 weeks of age is 80%.